Bemberg’s Third Sex: Argentine Mothers at the Dawn of Democracy - Williams, Bruce (Cinémas, 2004)
AbstractThe early features of Argentine director María Luisa Bemberg, Momentos and Señora de nadie, underscore the deployment of an ideology of motherhood in service of bourgeois social structure and military dictatorship. In these films, Bemberg posits the institution as balancing between containment and rebellion, her protagonists confronting the traditional ideological role of mother and asserting a stance against the repression of the waning dictatorship. Although entrenched in a conventional film discourse, these films set into motion the dynamics of diegetic radicalization which would define Bemberg’s subsequent work and would anticipate the redefinition of the social domain of the feminine for post-democracy Argentina.